Creation and Evaluation of a Pretertiary Artificial Intelligence (AI) Curriculum - Chiu, Thomas K. F.; Meng, Helen; Chai, Ching-Sing; King, Irwin; Wong, Savio; Yam, Yeung (IEEE transactions on education, 2022)
Contributions: The Chinese University of Hong Kong (CUHK)-Jockey Club AI for the Future Project (AI4Future) co-created the first pretertiary AI curriculum at the secondary school level for Hong Kong and evaluated its efficacy. This study added to the AI education community by introducing a new AI curriculum framework. The preposttest multifactors evaluation about students' perceptions of AI learning confirmed that the curriculum is effective in promoting AI learning. The teachers also confirmed the co-creation process enhanced their capacity to implement AI education. Background: AI4Future is a cross-sector project that engages five major partners-CUHK's Faculty of Engineering and Faculty of Education, secondary schools, Hong Kong government, and AI industry. A team of 14 professors collaborated with 17 principals and teachers from six secondary schools to co-create the curriculum. Research Questions: Would the curriculum significantly improve the student perceived competence, attitude, and motivation toward AI learning? How does the co-creation process benefit the implementation of the curriculum? Methodology: The participants were 335 students and eight teachers from the secondary schools. This study adopted a mix-method with quantitative data measures at pre- and post-questionnaires and qualitative data emphasizes teachers' perspectives on the co-creation process. Paired {t} -tests and ANCOVAs, and thematic analysis were used to analyze the data. Findings: 1) students perceived greater competence and developed a more positive attitude to learn AI and 2) the co-creation process enhanced teachers' knowledge in AI, as well as fostered teachers' autonomy in bringing the subject matter into their classrooms.